The Relationship Between The Satisfaction Of Patient For Hemodialysis Services In The Nephrology Unit Of Hngv, Dili, Timor-Leste - da Costa Fernandes, Manuel; Claudia da Costa Guterres, Ana; de Jesus Amaral, Isabel; Monteiro, Ermelinda; de Carvalho, Eugenia; António Bonito, Eva (Jurnal Syntax Fusion, 2023)
In today's era of globalization there are always changes in the needs of patients who always ask to get quality health services according to their wishes. According to the Global Burden of Disease in 2013, showed that the global prevalence of chronic kidney disease caused the death of 965.000 people worldwide. According to (ESRD, 2014), in Europe, it was stated that the number of hemodialysis patient was 79 patients, and according to research results obtained from respondent showed that, there where 45 (57,0%) of patients who were satisfied and 34 (43,0%) of patients who were dissatisfied with hemodialysis services. To know how the relationship between the satisfaction of patient for hemodialysis services in the nephrology unit of HNGV, Dili, Timor-Leste. This study used a quantitative correlation method with a cross sectional approach using non probability sampling techniques and total sampling techniques with a total of 98 respondents. According to the survey results obtained by 98 respondents who were satisfied with the services provided by nurses, the majority with satisfied category of 48 (49%) and minority with dissatisfied category of 10 (10%). Related to the services provided by nurses, the majority with good category of 45 (46%) and the minority with category less than 17 (17%). Based on the Spearman Rank statistic test showed that the result of p value 0.000 < 0.05, with a coefficient r= 0.647 means that there is a relationship between independent and dependent variable that category as a strong relationship. The result of this research demonstrates that there is a strong relationship between independent and dependent variable.